Analisis Permasalahan Calistung Pada Siswa Kelas III SD Muhammadiyah Birrul Walidain - Imamuddin, Ahmad Ridlwan; Kurniawan, Bagas; Riswari, Lovika Ardana (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2024)
This study aims to analyze calistung problems in third-grade students of SD Muhammadiyah Birrul Walidain. This research is a type of descriptive qualitative research that seeks an in-depth understanding of natural social phenomena. The data collection technique used is purposive sampling technique through interview methods, documentation, and direct observation. Based on the data obtained from the results of the study, it shows that out of 26 students in the class, there is one male student named Bima Aditya who still has difficulty in reading, writing, and counting due to a lack of learning experience at home, less innovative learning from teachers and lack of attention from parents and teachers to improve calistung skills in children. Therefore, teachers are required to be able to find innovations in learning strategies and implement differentiated learning to understand and differentiate students' learning styles from one another.